Feline sporotrichosis: occurrence in the Metropolitan Region of the municipality of Recife and anatomical distribution of lesions on cats’ body - Edson Moura da Silva; Luiz Felipe de Araújo França; Jéssica Cardoso Pessoa de Oliveira; Gílcia Aparecida de Carvalho; Daniel Dantas Moreira Gomes; José Wilton Pinheiro Júnior; Rafael Antonio Nascimento Ramos (Medicina Veterinária)
Sporotrichosis is a fungal infection of worldwide importance caused by a saprophyte fungus of the genus Sporothrix. The objective of this study was to report the occurrence of feline sporotrichosis in the Metropolitan Region of the city of Recife and the anatomical distribution of lesions on the bodies of cats. Stray cats (n=100) with suggestive sporotrichosis lesions were examined. Material from the lesion was collected from all patients using an imprint and/or sterile swab for cytology. The material was placed on a glass slide and stained using rapid panoptic staining. Data on the localization of each skin lesion were recorded, and cigar-shaped yeast structures were searched at the microscopical examination. A heat map graphically represented the anatomical distribution of each lesion. In 70% (70/100) of samples were visualized fungal structure compatible with Sporothrix spp. There was a predominance of positive males (?2=6.691; p=0.0097). Skin lesions related to Sporothrix spp. infections were unevenly distributed throughout the animal's body. Based on the interpolation of data, the chance for detecting lesions was higher on the nose, anterior paw, and ears than on other body sites (H=40.0043; p=0.0000). Because of the high positivity in these cats, measures of health vigilance are imperative to reduce the risk of animal and human infection.